The role of the social worker in healthcare in the context of the implementation of the ICF in Ukraine - Blyzniuk V. V.; Teriukhanova I. M. (Український соціум)
The article discusses the latest approaches to the role and place of social workers in healthcare, related to the transition of many countries, including Ukraine, to a new disability assessment model – bio-psychosocial. The aim of the research is to determine the role of a social worker in multidisciplinary teams providing rehabilitation assistance in a rehabilitation facility, and to substantiate the optimal tool for assessing the degree of disability of individuals with limitations in daily functioning. The considered methods of disability assessment in different countries made it possible to state the application of different approaches and the possibility of involving social workers in this process. It is stated, that the implementation of ICF principles in the health care system significantly increases the role of social workers, who assess the level of limitation of a person’s vital activities in separate domains. The authors show that there is currently no universal tool for assessing ICF domains. Most countries develop their own assessment tools for use in the context of social policy, but the basis is the universal health and disability assessment tool developed by WHO experts (WHO Disability Assessment Schedule, WHODAS). The article analyzes the experience of Korea, Taiwan, the Netherlands, and Sweden regarding the assessment of violations carried out by a medical social worker. The necessity and expediency of the participation of social workers as part of an interdisciplinary team is proved. It is substantiated that the new role of the social worker in the field of health care is that he/she, as a member of the multidisciplinary team of the rehabilitation institution, should participate in the process of determining disability in addition to assessing social needs. The authors proposed a tool for assessing the degree of limitation of a person’s vital activities in accordance with WHODAS 2.0, which will contribute to the effective implementation of the ICF in Ukraine.